Poly (o-Phenylenediamine-GO-TiO2) nanocomposite: Modulation, characterization and thermodynamic calculations on its H2 storage capacity - Majeed, Abdulwahhab H; Hussain, Dhia H; Al-Tikrity, Emaad T. Bakir; Alheety, Mustafa A (Chemical Data Collections, 2020)
This work concludes the synthesis and characterization of a new tri-components nanocomposite. All three starting materials (graphene oxide, TiO2, poly (o-phenylenediamine)) were prepared in our laboratory and the results showed that graphene oxide (GO) was present in the form of nanosheets and the titanium oxide (TiO2) gave a rod-like nanostructure (19–30 nm), while the poly (o-phenylenediamine) (PoPDA) showed an irregular nano-sized structure (40–250 nm). The prepared nanocomposite PoPDA-GO-TiO2, synthesized in a bi-step chemical reaction and it was diagnosed using different techniques: FTIR, XRD, TGA, SEM and TEM. These techniques prove the success of the reaction between all three starting materials. The resulting nanocomposite was successfully used for hydrogen uptake capacity and the results prove that PoPDA-GO-TiO2 nanocomposite shows an excellent ability to store the hydrogen gas (5.2 wt% under 85.5771, 129.8900 and 167.9900 bar at 77, 223 and 273 K, respectively. Furthermore, enthalpy and entropy were calculated to be -2.8478 KJ/mol H2 and -14.910 J/mol H2. K, respectively. [Display omitted]